Polyether-ether-ketone composite material as well as preparation method and application thereof
By combining ZIF-62 with polyether ether ketone and 3D printing, a uniform transfer film is formed, which solves the problem of insufficient wear resistance of polyether ether ketone materials and improves its application performance in humanoid robots and other fields.
Patent Information
- Application Number
- CN202510691110.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-27
- Publication Date
- 2025-08-12
AI Technical Summary
The wear resistance of existing polyether ether ketone materials is insufficient, which limits its application in humanoid robots and other fields.
ZIF-62 is combined with polyether ether ketone, and ZIF-62/polyether ether ketone composite material is prepared through 3D printing technology. The meltability of ZIF-62 is used to improve the interface bonding performance, and a uniform transfer film is formed during the friction process to reduce wear.
It significantly improves the wear resistance and tribological properties of polyether etherketone composite materials, enhances the mechanical properties, and reduces the scratches between the steel ring and the PEEK matrix.
Smart Images

Figure CN120464172A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wear-resistant materials, and in particular to a polyetheretherketone composite material and a preparation method and application thereof. Background Art
[0002] With the rapid development of science and technology, robotics, as a key branch of modern technology, is undergoing unprecedented transformation. Humanoid robots, a cutting-edge product in this field, have become a hot topic of research due to their unique humanoid appearance and mobility. Among the many key components of humanoid robots, lightweight, highly wear-resistant, and environmentally adaptable moving parts play a crucial role in their performance.
[0003] Among many materials, polyetheretherketone (PEEK) has great potential for application in robotics due to its excellent mechanical properties and thermal stability. However, despite its many advantages, PEEK's wear resistance still needs to be further improved. Summary of the Invention
[0004] In view of this, the object of the present invention is to provide a polyetheretherketone composite material and its preparation method and application. The polyetheretherketone composite material provided by the present invention has excellent wear resistance.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a polyetheretherketone composite material, comprising the following components in weight fractions:
[0007] Polyetheretherketone 97-99% and ZIF-62 1-3%.
[0008] The present invention also provides a method for preparing the polyetheretherketone composite material described in the above technical solution, comprising the following steps:
[0009] mixing polyetheretherketone powder and ZIF-62 powder to obtain a mixed powder;
[0010] Extruding the mixed powder to obtain a composite wire;
[0011] The composite wire material is used as a raw material to perform 3D printing to obtain the polyetheretherketone composite material.
[0012] Preferably, the method for preparing the ZIF-62 powder comprises the following steps:
[0013] The zinc salt, imidazole, benzimidazole and solvent are mixed, and coordination reaction is carried out under ball milling conditions to obtain the ZIF-62 powder.
[0014] Preferably, the molar ratio of zinc, imidazole and benzimidazole in the zinc salt is 1:0-2:0-2, wherein the molar amount of imidazole and benzimidazole is not 0;
[0015] The zinc salt comprises zinc hydroxide and zinc acetate, and the molar percentage of zinc acetate in the zinc salt is 20-40%.
[0016] Preferably, the rotation speed of the ball mill is 300-600 r / min, and the coordination reaction time is 0.5-3 h.
[0017] Preferably, the mixing is mechanical mixing, and after the mixing, drying is also included.
[0018] Preferably, the diameter of the composite wire is 1.75±0.1 mm.
[0019] Preferably, the extrusion molding parameters include: the temperature of zone 1 is 300-330°C, the temperature of zone 2 is 350-390°C, the temperature of zone 3 is 350-390°C; and the head temperature is 340-390°C.
[0020] Preferably, the 3D printing parameters include: nozzle temperature of 390-450°C, base plate temperature of 25-220°C, cavity temperature of 25-220°C, nozzle diameter of 0.2-0.4 mm, printing speed of 20-40 mm / s, layer thickness of 0.1-0.3 mm, and filling density of 80-100%.
[0021] The present invention also provides the use of the polyetheretherketone composite material described in the above technical solution or the polyetheretherketone composite material prepared by the preparation method described in the above technical solution in friction materials.
[0022] The invention provides a polyetheretherketone composite material.
[0023] The present invention combines ZIF-62 with PEEK to produce a polyetheretherketone (PEEK) composite material. Compared to the PEEK matrix, the meltability of ZIF-62 significantly improves the interfacial bonding performance between filaments during 3D printing, thereby promoting the improvement of the mechanical properties of the PEEK composite material. Furthermore, ZIF-62 can undergo a friction reaction with the surface of the steel ring, and the friction products form a uniform and continuous transfer film, which reduces the plowing and cutting effects of the dual surface micro-asperities on the wear surface of the composite material, effectively reducing the scratching between the steel ring and the PEEK matrix, and enhancing the tribological properties of the PEEK composite material. Based on the above factors, the ZIF-62 / PEEK composite material has excellent wear resistance.
[0024] The present invention also provides a method for preparing the polyetheretherketone composite material described in the above technical solution. The preparation method provided by the present invention is simple and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The XRD patterns of ZIF-62 obtained in simulation and Example 1 are shown;
[0026] Figure 2 The scanning electron microscope image of the ZIF-62 crystal obtained in Example 1 is
[0027] Figure 3 Schematic diagram of the tribological performance test process;
[0028] Figure 4 This is an SEM image of the worn surface of the polyetheretherketone composite material obtained in Example 4 after a 2-h tribological performance test (4 MPa, speed of 1 m / s);
[0029] Figure 5 This is a scanning electron microscope image of the transfer film on the dual pair after the tribological performance test (4 MPa, speed of 1 m / s) of the polyetheretherketone composite material obtained in Example 4 for 2 hours;
[0030] Figure 6 This is the EDS element distribution diagram of the transfer film on the dual side after the tribological performance test (4 MPa, speed of 1 m / s) of the polyetheretherketone composite material obtained in Example 4 for 2 hours. DETAILED DESCRIPTION
[0031] The present invention provides a polyetheretherketone composite material, comprising the following components in weight fractions:
[0032] Polyetheretherketone 97-99% and ZIF-62 1-3%.
[0033] Unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.
[0034] The polyetheretherketone composite material provided by the present invention comprises 97-99% polyetheretherketone by mass, preferably 97%, 97.5%, 98%, 98.5%, or 99%. In the present invention, polyetheretherketone (PEEK) has great potential application in the field of robotics due to its excellent mechanical properties and thermal stability as a lightweight material with excellent performance.
[0035] The polyetheretherketone composite material provided by the present invention includes ZIF-62 with a mass fraction of 1 to 3%, preferably 1%, 1.5%, 2%, 2.5% or 3%. In the present invention, ZIF-62 is a typical MOFs material, an organic-inorganic hybrid material, with a high specific surface area and an adjustable pore structure. It is different from traditional inorganic porous materials such as zeolites, and is also different from general organic complexes. Instead, it has the rigidity of inorganic materials and the flexibility of organic materials. The rich organic ligands on its surface are conducive to enhancing its compatibility with the polymer material matrix, making it uniformly dispersed and forming a good interface bond with the matrix. At the same time, the solubility of ZIF-62 is conducive to improving the interfacial bonding performance between filaments during 3D printing, thereby promoting the improvement of the mechanical properties of the polyetheretherketone composite material. At the same time, ZIF-62 can undergo a friction reaction with the steel ring surface, and the friction products form a uniform and continuous transfer film, which reduces the plowing and cutting effects of the dual surface micro-asperities on the composite's wear surface. This effectively reduces the scratching between the steel ring and the PEEK matrix, and enhances the tribological properties of the PEEK composite. Based on these factors, the ZIF-62 / PEEK composite has excellent friction properties.
[0036] The present invention also provides a method for preparing the polyetheretherketone composite material described in the above technical solution, comprising the following steps:
[0037] mixing polyetheretherketone powder and ZIF-62 powder to obtain a mixed powder;
[0038] Extruding the mixed powder to obtain a composite wire;
[0039] The composite wire material is used as a raw material to perform 3D printing to obtain the polyetheretherketone composite material.
[0040] The present invention mixes polyetheretherketone powder and ZIF-62 powder to obtain mixed powder.
[0041] In the present invention, the particle size of the polyetheretherketone powder is preferably 200 mesh.
[0042] In the present invention, the particle size of the ZIF-62 powder is preferably 1 to 6 μm.
[0043] In the present invention, the preparation method of the ZIF-62 powder preferably comprises the following steps:
[0044] The zinc salt, imidazole, benzimidazole and solvent are mixed, and coordination reaction is carried out under ball milling conditions to obtain the ZIF-62 powder.
[0045] In the present invention, the zinc salt preferably includes zinc hydroxide (Zn(OH)2) and zinc acetate (Zn(OAc)2); the zinc acetate is further preferably zinc acetate dihydrate (Zn(OAc)2·2H2O). In the present invention, the molar percentage of zinc acetate in the zinc salt is preferably 20-40%, specifically preferably 20%, 25%, 30%, 35% or 40%.
[0046] In the present invention, the molar ratio of zinc, imidazole and benzimidazole in the zinc salt is preferably 1:0-2:0-2, wherein the molar amount of imidazole and benzimidazole is not 0; more preferably 1:0.25-1.75:0.25-1.75, specifically preferably 1:1.75:0.25, 1:1.5:0.5 or 1:1.25:0.75.
[0047] In the present invention, the solvent preferably includes one or more of N,N-dimethylformamide (DMF) and methanol. In the present invention, the ratio of the zinc salt to the solvent is 2-10 g:1-10 mL.
[0048] In the present invention, the ball milling speed is preferably 300 to 600 r / min, specifically preferably 300 r / min, 350 r / min, 400 r / min, 450 r / min, 500 r / min, 550 r / min or 600 r / min. In the present invention, the ball milling is preferably carried out on a planetary ball mill. In the present invention, the coordination reaction time is preferably 0.5 to 3 hours, specifically preferably 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours.
[0049] After the coordination reaction, the present invention preferably further comprises: washing and drying the obtained material in sequence to obtain the ZIF-62 powder; the washing reagent preferably comprises DMF, the washing method is preferably centrifugal washing, and the number of washings is preferably 1 to 3 times, specifically preferably 1 time, 2 times or 3 times. In the present invention, the drying temperature is preferably 80 to 120°C, specifically preferably 80°C, 90°C, 100°C, 110°C or 120°C; the drying time is preferably 10 to 15 hours, specifically preferably 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours; and the drying is preferably carried out in an oven.
[0050] In the present invention, ZIF-62 is a metal organic framework (MOFs) compound composed of zinc ions (Zn 2+ ) is connected to two imidazole ligands (usually imidazole (Im) and benzimidazole (BIm)) through coordination bonds to form a three-dimensional porous structure. Among them, the metal center is zinc (Zn), and the organic ligands are imidazole (Im) and benzimidazole (BIm). Each Zn 2+It forms tetrahedral coordination with the nitrogen atom of the imidazole ligand, and each nitrogen atom of the imidazole or benzimidazole ligand forms a tetrahedral coordination with one Zn 2+ coordination, while the other nitrogen atom of the ligand is connected to another Zn 2+ , forming an extended three-dimensional network, with alternating connections of ligands forming four-membered or six-membered ring channels. ZIF-62 typically has a GME topology (similar to the zeolite chabazite structure).
[0051] In the present invention, the polyetheretherketone powder and the ZIF-62 powder are preferably mixed mechanically, and the mechanical mixing is preferably carried out in a mixer. The present invention does not specifically limit the parameters of the mechanical mixing, as long as the two materials can be mixed evenly.
[0052] After the mixing, the present invention preferably further comprises drying; the drying temperature is preferably 80-120°C, specifically preferably 80°C, 90°C, 100°C, 110°C or 120°C; the drying time is preferably 12-36h, specifically preferably 12h, 18h, 24h, 30h or 36h.
[0053] After obtaining the mixed powder, the present invention extrudes the mixed powder into a shape to obtain a composite wire material.
[0054] In the present invention, the extrusion molding parameters include: the temperature of the first zone is preferably 300-330 ° C, specifically preferably 300 ° C, 305 ° C, 310 ° C, 315 ° C, 320 ° C, 325 ° C or 330 ° C; the temperature of the second zone is preferably 350-390 ° C, specifically preferably 350 ° C, 355 ° C, 360 ° C, 365 ° C, 370 ° C, 375 ° C, 380 ° C, 385 ° C or 390 ° C; the temperature of the third zone is preferably 350-390 ° C, specifically preferably 350 ° C, 355 ° C, 360 ° C, 365 ° C, 370 ° C, 375 ° C, 380 ° C, 385 ° C or 390 ° C; The zone temperature is preferably 350-390°C, specifically 350°C, 355°C, 360°C, 365°C, 370°C, 375°C, 380°C, 385°C or 390°C; the head temperature is preferably 340-390°C, specifically 340°C, 345°C, 350°C, 355°C, 360°C, 365°C, 370°C, 375°C, 380°C, 385°C or 390°C.
[0055] In the present invention, the extrusion molding is preferably performed under a protective atmosphere, and the protective atmosphere preferably includes nitrogen.
[0056] In the present invention, the extrusion molding is preferably carried out in a twin-screw extruder. In the present invention, the diameter of the composite wire is preferably 1.75±0.1 mm.
[0057] After the extrusion molding, the present invention preferably further comprises: drying the obtained extrudate to obtain the composite filament. In the present invention, the drying temperature is preferably 80-120°C, specifically preferably 80°C, 90°C, 100°C, 110°C, or 120°C; the drying time is preferably 8-12 hours, specifically preferably 8 hours, 10 hours, or 12 hours; and the drying is preferably performed in a drying oven.
[0058] After obtaining the composite wire material, the present invention uses the composite wire material as a raw material to perform 3D printing to obtain the polyetheretherketone composite material.
[0059] In the present invention, the parameters of the 3D printing include: the nozzle temperature is preferably 390-450°C, specifically preferably 390°C, 400°C, 410°C, 420°C, 430°C, 440°C or 450°C; the base plate temperature is preferably 25-220°C, specifically preferably 25°C, 50°C, 75°C, 100°C, 125°C, 150°C, 175°C, 200°C or 220°C; the cavity temperature is preferably 25-220°C, specifically preferably 25°C, 50°C, 75°C, 100°C, 125°C, 150°C, 175°C, 200°C or 220°C; the nozzle straight The diameter is preferably 0.2-0.4 mm, specifically preferably 0.2 mm, 0.25 mm, 0.3 mm, 0.35 mm or 0.4 mm; the printing speed is preferably 20-40 mm / s, specifically preferably 20 mm / s, 25 mm / s, 30 mm / s, 35 mm / s or 40 mm / s; the layer thickness is preferably 0.1-0.3 mm, specifically preferably 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm or 0.3 mm; the filling density is preferably 80-100%, specifically preferably 80%, 85%, 90%, 95% or 100%.
[0060] In the present invention, the 3D printing is preferably performed on a fused deposition 3D printer.
[0061] The present invention also provides the use of the polyetheretherketone composite material described in the above technical solution or the polyetheretherketone composite material prepared by the preparation method described in the above technical solution in friction materials.
[0062] The present invention does not specifically limit the application mode of the polyetheretherketone composite material, and those skilled in the art can configure it according to actual needs.
[0063] The polyetheretherketone composite material provided by the present invention, its preparation method and application are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0064] The polyetheretherketone powder used in the following examples is 550PF-200 polyetheretherketone powder produced by Jilin Zhongyan Polymer Materials Co., Ltd.
[0065] Example 1
[0066] First, using an analytical balance, 3.5 g (0.035 mol) of Zn(OH)2, 3.3 g (0.015 mol) of Zn(OAc)2·2H2O, imidazole (Im) and benzimidazole (BIm) were weighed in a molar ratio of Zn, Im, and BIm of 1:1.75:0.25, and 5 mL of N,N-dimethylformamide (DMF) were added to an agate jar. The jar was then sealed and placed in a planetary ball mill, where it was milled at 400 r / min for 1 hour. After ball milling, the product was collected and washed three times by centrifugation with DMF. Finally, the washed product was dried in an oven at 100°C for 12 hours to obtain ZIF-62 as a white powder.
[0067] Figure 1 For simulation (corresponding to Figure 1 Simulated ZIF-62 in Example 1) and ZIF-62 obtained in Example 1 (corresponding to Figure 1 The XRD spectrum of Synthesized ZIF-62 in Figure 1 It can be seen that the spectrum of synthesized ZIF-62 is basically consistent with the simulated spectrum, proving the feasibility of the synthesis method.
[0068] Figure 2 The scanning electron microscope image of the ZIF-62 crystal obtained in Example 1 is shown in FIG. Figure 2 It can be seen that the particle size of ZIF-62 crystals is distributed in the range of 1 to 6 μm.
[0069] One part by weight of ZIF-62 was weighed using an analytical balance and added to a high-speed mixer along with 99 parts by weight of polyetheretherketone (PEEK) for thorough mechanical mixing. The mixture was dried at 100°C for 24 hours to obtain a mixed powder. Under nitrogen protection, the mixed powder was extruded into a ZIF-62 / PEEK composite filament with a diameter of 1.75±0.1mm using a twin-screw extruder. The temperatures of the various zones of the twin-screw extruder were set as follows: Zone 1 at 310°C, Zone 2 at 370°C, Zone 3 at 360°C, and the die head at 350°C. Subsequently, the composite filaments were dried in a drying oven at 100°C for 10 hours and then printed using a fused deposition model 3D printer to obtain a ZIF-62 / polyetheretherketone composite material. The printing parameters were set as follows: nozzle temperature of 440°C, base plate temperature of 220°C, cavity temperature of 200°C, nozzle diameter of 0.4mm, printing speed of 30mm / s, layer thickness of 0.2mm, and filling density of 100%.
[0070] XRD testing of the obtained ZIF-62 / polyetheretherketone composite material proved that after high-temperature melting treatment, ZIF-62 transformed from a crystalline structure to an amorphous structure.
[0071] Example 2
[0072] ZIF-62 was prepared according to the method of Example 1.
[0073] Two parts by weight of ZIF-62 were weighed on an analytical balance and added to a high-speed mixer along with 98 parts by weight of polyetheretherketone (PEEK) for thorough mechanical mixing. The mixture was dried at 100°C to obtain a mixed powder. Under nitrogen protection, the mixed powder was extruded using a twin-screw extruder to produce ZIF-62 / PEEK composite filaments with a diameter of 1.75±0.1 mm. The temperatures in each zone of the twin-screw extruder were set as follows: zone 1 at 310°C, zone 2 at 370°C, zone 3 at 360°C, and the die head at 350°C. Subsequently, the composite filament was dried in a drying oven at 100°C for 10 hours and then printed using a fused deposition model 3D printer to obtain a ZIF-62 / polyetheretherketone composite material. The parameters during the printing process were set as follows: nozzle temperature of 440°C, base plate temperature of 220°C, cavity temperature of 200°C, nozzle diameter of 0.4mm, printing speed of 30mm / s, layer thickness of 0.2mm, and filling density of 100%.
[0074] Example 3
[0075] ZIF-62 was prepared according to the method of Example 1.
[0076] 2.5 parts by weight of ZIF-62 were weighed on an analytical balance and added to a high-speed mixer along with 97.5 parts by weight of polyetheretherketone (PEEK) for thorough mechanical mixing. The mixture was dried at 100°C to obtain a mixed powder. Under nitrogen protection, the mixed powder was extruded using a twin-screw extruder to produce ZIF-62 / PEEK composite filaments with a diameter of 1.75±0.1 mm. The temperatures of the twin-screw extruder zones were set as follows: zone 1 at 310°C, zone 2 at 370°C, zone 3 at 360°C, and the die head at 350°C. Subsequently, the composite filament was dried in a drying oven at 100°C for 10 hours and then printed using a fused deposition model 3D printer to obtain a ZIF-62 / polyetheretherketone composite material. The parameters during the printing process were set as follows: nozzle temperature of 440°C, base plate temperature of 220°C, cavity temperature of 200°C, nozzle diameter of 0.4mm, printing speed of 30mm / s, layer thickness of 0.2mm, and filling density of 100%.
[0077] Example 4
[0078] ZIF-62 was prepared according to the method of Example 1.
[0079] 3 parts by weight of ZIF-62 were weighed using an analytical balance and added to a high-speed mixer along with 97 parts by weight of polyetheretherketone (PEEK) for thorough mechanical mixing. The mixture was dried at 100°C to obtain a mixed powder. Under nitrogen protection, the mixed powder was extruded using a twin-screw extruder to produce ZIF-62 / PEEK composite filaments with a diameter of 1.75±0.1 mm. The temperatures in each zone of the twin-screw extruder were set as follows: zone 1 at 310°C, zone 2 at 370°C, zone 3 at 360°C, and the die head at 350°C. Subsequently, the composite filament was dried in a drying oven at 100°C for 10 hours and then printed using a fused deposition model 3D printer to obtain a ZIF-62 / polyetheretherketone composite material. The parameters during the printing process were set as follows: nozzle temperature of 440°C, base plate temperature of 220°C, cavity temperature of 200°C, nozzle diameter of 0.4mm, printing speed of 30mm / s, layer thickness of 0.2mm, and filling density of 100%.
[0080] Comparative Example 1 (without ZIF-62)
[0081] 100 parts by weight of polyetheretherketone (PEEK) were accurately weighed on an analytical balance and dried in a drying oven at 100°C. The dried PEEK was then extruded into filaments with a diameter of 1.75±0.1 mm using a twin-screw extruder. The temperatures of the extruder zones were set as follows: zone 1 at 310°C, zone 2 at 370°C, zone 3 at 360°C, and die head temperature at 350°C. The PEEK filaments were further dried in a drying oven at 100°C for 10 hours to ensure stable performance. Finally, the filaments were printed into PEEK sample materials using a fused deposition model 3D printer. The printing parameters were as follows: nozzle temperature of 440°C, base plate temperature of 220°C, chamber temperature of 200°C, nozzle diameter of 0.4 mm, printing speed of 30 mm / s, layer thickness of 0.2 mm, and infill density of 100%.
[0082] Example 5
[0083] The difference from Example 4 is that during the preparation of ZIF-62, the molar ratio of zinc salt (wherein the zinc salt includes Zn(OH)2 0.035 mol and Zn(OAc)2·2H2O 0.015 mol), imidazole and benzimidazole is controlled to be 1:1.5:0.5.
[0084] Example 6
[0085] The difference from Example 4 is that during the preparation of ZIF-62, the molar ratio of zinc salt (wherein the zinc salt includes Zn(OH)2 0.035 mol and Zn(OAc)2·2H2O 0.015 mol), imidazole and benzimidazole is controlled to be 1:1.25:0.75.
[0086] The materials obtained in the examples and comparative examples were subjected to bending tests and tensile tests at room temperature. The bending tests and tensile tests were conducted in accordance with GB / T 9341-2008 and GB / T 1040.1-2006 standards, with the bending test speed set at 2 mm / min and the tensile test speed set at 1 mm / min.
[0087] The tribological properties of the materials obtained in the examples and comparative examples were evaluated with reference to GB / T 12444-2006. Specifically, the pin-ring contact mode was adopted, such as Figure 3 The experimental conditions were set as a load of 4 MPa and a speed of 1 m / s. Before the friction test, the 3D printed ZIF-62 / PEEK composite pin (size 4×4×12 mm) was 3 ) were pre-ground to ensure a good match with the corresponding GCr15 steel ring. Each friction test lasted 2 hours. The coefficient of friction (COF) was the average value after the friction entered the stable stage. The average friction coefficient was the average of the friction coefficients of three parallel tests. In addition, the wear rate (Ws) of the friction material was calculated using Equation 1:
[0088]
[0089] Where Δm represents the mass loss of the pin sample before and after the test, ρ is the density of the sample, F is the normal load, and L is the total sliding distance. The average wear rate is the average of the wear rates of three parallel experiments.
[0090] The results of bending test, tensile test and tribological properties are shown in Table 1.
[0091] Table 1 Performance indicators of the composite materials obtained in the examples and comparative examples
[0092]
[0093] The tribological properties of the material obtained in Example 4 were evaluated with reference to GB / T 12444-2006. Specifically, the pin-ring contact mode was adopted, such as Figure 3 The experimental conditions are shown in Table 2. Before the friction test, the 3D printed ZIF-62 / PEEK composite pin (size 4×4×12mm 3) were pre-ground to ensure a good match with the corresponding GCr15 steel ring. Each friction test lasted 2 hours. The coefficient of friction (COF) was the average value after the friction reached the stable stage. In addition, the wear rate (Ws) of the friction material was calculated using Equation 1. The results are shown in Table 2.
[0094] Table 2 Friction properties of the composite materials obtained in Example 4 under different conditions
[0095] Average volume wear rate Average friction coefficient 2MPa load, 1m / s speed Example 4 <![CDATA[4.62×10 -6 mm 3 / Nm]]> 0.43 6MPa load, 1m / s speed Example 4 <![CDATA[8.28×10 -6 mm 3 / Nm]]> 0.35 8MPa load, 1m / s speed Example 4 <![CDATA[8.35×10 -6 mm 3 / Nm]]> 0.31 10MPa load, 1m / s speed Example 4 <![CDATA[1.02×10 -5 mm 3 / Nm]]> 0.38 4MPa load, 0.5m / s speed Example 4 <![CDATA[4.52×10 -6 mm 3 / Nm]]> 0.30 4MPa load, 1.5m / s speed Example 4 <![CDATA[9.45×10 -6 mm 3 / Nm]]> 0.36 4MPa load, 2m / s speed Example 4 <![CDATA[9.46×10 -6 mm 3 / Nm]]> 0.39
[0096] Figure 4 The SEM image of the wear surface of the polyetheretherketone composite material obtained in Example 4 after the tribological performance test (4MPa, speed of 1m / s) for 2h; Figure 4 It can be observed that the worn surface is smooth and no obvious furrows appear.
[0097] Figure 5 This is a scanning electron microscope image of the transfer film on the dual pair after the tribological performance test (4 MPa, speed of 1 m / s) of the polyetheretherketone composite material obtained in Example 4 for 2 hours; Figure 5 It is clearly shown that the polyetheretherketone composite material forms a uniform and continuous transfer film on the metal dual surface, which reduces the wear rate of the polyetheretherketone composite material and thus improves the tribological properties of the polyetheretherketone composite material.
[0098] Figure 6 The EDS element distribution diagram of the transfer film on the dual side after the tribological performance test (4MPa, speed 1m / s) of the polyetheretherketone composite material obtained in Example 4 for 2h. Figure 6 The presence of elements such as Zn and N was detected in the transfer film on the metal pair, indicating that the formation of the transfer film is primarily due to the participation of the metal elements in ZIF-62 in its construction. The formation of the transfer film further reduces the plowing and cutting effects of the micro-asperities on the metal pair's surface on the wear surface of the polyetheretherketone composite. Based on this mechanism, the tribological properties of the polyetheretherketone composite are effectively improved.
[0099] A comparison of mechanical properties shows that when ZIF-62 is added to PEEK, the 3D-printed ZIF-62 / PEEK composite material exhibits a certain degree of increase in flexural and tensile strength compared to PEEK. Compared to the PEEK matrix, the ZIF-62 / PEEK composite material exhibits better melting and bonding between the PEEK matrix and ZIF-62 due to the filler's meltability, enabling effective stress transfer, thereby improving the mechanical properties of the composite material. A study of the tribological properties of 3D-printed ZIF-62 / PEEK composite materials shows that the addition of an appropriate amount of ZIF-62 facilitates the formation of a continuous and uniform transfer film, significantly improving the tribological properties of the 3D-printed ZIF-62 / PEEK composite material.
[0100] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A polyetheretherketone composite material, characterized in that The following components are included in mass fraction: Polyetheretherketone 97-99% and ZIF-62 1-3%.
2. The method for preparing the polyetheretherketone composite material according to claim 1, characterized in that: The following steps are involved: mixing polyetheretherketone powder and ZIF-62 powder to obtain a mixed powder; Extruding the mixed powder to obtain a composite wire; The composite wire material is used as a raw material to perform 3D printing to obtain the polyetheretherketone composite material.
3. The preparation method according to claim 2, characterized in that The preparation method of the ZIF-62 powder comprises the following steps: The zinc salt, imidazole, benzimidazole and solvent are mixed, and coordination reaction is carried out under ball milling conditions to obtain the ZIF-62 powder.
4. The preparation method according to claim 3, characterized in that The molar ratio of zinc, imidazole and benzimidazole in the zinc salt is 1:0 to 2:0 to 2, wherein the molar amount of imidazole and benzimidazole is not 0; The zinc salt comprises zinc hydroxide and zinc acetate, and the molar percentage of zinc acetate in the zinc salt is 20-40%.
5. The preparation method according to claim 3 or 4, characterized in that The ball mill has a rotation speed of 300 to 600 r / min, and the coordination reaction time is 0.5 to 3 hours.
6. The preparation method according to claim 2, characterized in that The mixing is mechanical mixing, and after the mixing, drying is also included.
7. The preparation method according to claim 2, characterized in that The diameter of the composite wire is 1.75±0.1 mm.
8. The preparation method according to claim 2 or 7, characterized in that The extrusion molding parameters include: the temperature of the first zone is 300-330°C, the temperature of the second zone is 350-390°C, the temperature of the third zone is 350-390°C; and the head temperature is 340-390°C.
9. The preparation method according to claim 2, characterized in that The 3D printing parameters include: nozzle temperature of 390-450°C, base plate temperature of 25-220°C, cavity temperature of 25-220°C, nozzle diameter of 0.2-0.4mm, printing speed of 20-40mm / s, layer thickness of 0.1-0.3mm, and filling density of 80-100%.
10. Use of the polyetheretherketone composite material according to claim 1 or the polyetheretherketone composite material prepared by the preparation method according to any one of claims 2 to 9 in friction materials.